Latent variable models : An introduction to factor, path, and structural analysis - Loehlin, John C. (Hillsdale, NJ : Lawrence Erlbaum Associates, 1987)
This book is intended as an introduction to an exciting growth area in social science methodology--the use of multiple-latent-variable models. Psychologists and other social scientists have long been familiar with one subvariety of such modeling, factor analysis--more properly, exploratory factor analysis. In recent decades, confirmatory factor analysis, path analysis, and structural equation modeling have come out of specialized niches and are making their bid to become basic tools in the research repertoire of the social scientist, particularly the one who is forced to deal with complex real-life phenomena in the round: the sociologist, the political scientist, the social, educational, clinical, industrial, personality or developmental psychologist, the marketing researcher, and the like.
Path models in factor, path, and structural analysisFitting path modelsVarieties of path and structural models--IVarieties of path and structural models--IIModels with reciprocal influences and correlated errorsModels of events over timeModels comparing different groupsExploratory factor analysis--I: Extracting the factorsExploring factor analysis--II: Transforming the factors to simpler structureOrthogonal transformation--quartimax and varimaxOblique transformationsFactor rotation programs--SPSS, BMDP, and SASExtensions of latent variable analysisAppendicesA. Simple matrix operationsB. IPSOLC. Derivation of matrix version of path equationsD. Alpha and canonical factor extraction--a worked exampleE. Examples of input for factor extraction by SPSS, BMDP, and SASF. Data matrix for Thurstone's box problemG. Table of chi square
Bibliografija
Kazalo
Keywords: faktorska analiza; analiza puta; strukturalno modeliranje